Analisis Dampak Parkir Liar terhadap Tingkat Kunjungan Konsumen pada Usaha Kecil dan Menengah (UKM) di Kota Bandar Lampung - Alvi Mevia Elbatista; Abizar Abizar; Ulil Albab (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
This study examines how illegal parking affects the level of customer visits to small and medium enterprises (SMEs) in Bandar Lampung City, with a particular focus on the Saburai Field area. The study conducted interviews with SME owners and customers to collect data using a descriptive qualitative research method. The results showed that illegal parking has varying impacts on the number of customer visits; some business owners said that there was no impact, while others said that there was an impact. From the customer's perspective, illegal parking significantly disrupts the comfort and safety of shopping, which may change their customer visit patterns. Illegal parking is generally considered to disrupt consumers' shopping experience, which may influence their decision to visit nearby SMEs, although the impacts vary. This study emphasizes that more organized parking management is essential to improving the business environment and competitiveness of small and medium enterprises in Bandar Lampung City.